Penatalaksanaan Fisioterapi Pada Kondisi Post Stroke Di RSUD Salatiga - Sulistiyawan, Ary; , Totok Budi Santoso, S.Fis., MPH (2014)
Background: Stroke is an acute neurological dysfunction caused by circulatory disorders of the brain, in which the sign of symptoms suddenly and rapidly accordance with the focal areas of the brain are disturbed. These complaints can be handled by physiotherapist. Methods: The method in this case is to use infrared modalities, therapeutic exercise and functional movement exercises, that are evaluated by the method of measuring the strength with the blank Muscle Examination, functional activity with the Katz Index, and balance with Sitting Balance Test. Objective: the above method to determine the benefits of infrared therapy modalities, therapeutic exercise and functional movement exercises to increase muscle strength, balance, and functional activity. Results: after 6 treatments, the result has showed increase of muscle strength in almost of all regions, the increase of the balance fromT1=2 becomes T6=3 on Sitting Balance Test, and an increase of the functional activity from G becomes E of the value. Conclusion: Infrared, therapeutic exercise and functional movement exercises can improve muscle strength, improve balance, and improve functional activities.